“Technological didactic resources to increase vocabulary in a virtual environment during pandemic at the Federico Froebel basic school year 2021-2022” - Calderón Guano, Jennifer Daniela (2022)
The English vocabulary is an essential part of learning it as a foreign language. It can help people to understand and communicate in the same language. In vocabulary learning, many traditional methods might be applied in this sub-skill, such as flashcards, memorization of words, etc. As it is known, technology has helped learn a new language, become a modern strategy, and increasingly assist in developing language skills. However, due to the pandemic (Covid-19) and the change of Education in a virtual mode, it has caused that the use of technological resources increased, and it is essential in English classes. For that reason, this research aims to analyze technological didactic resources that will help in vocabulary learning in the English language for students of primary schools who adopted a virtual mode in the classrooms. A bibliography search was done based on different authors that support technological tools as a new strategy to learn English vocabulary to reach this goal. Hence, a quantitative approach was applied, with a non-experimental transversal type of research and theoretical-descriptive methodology. The instrument used was the survey, which allowed the data collection, and it was involved in a sample of 70 learners for the Fourth-grade of a primary school. As a result of this proposal, technological didactic resources will benefit the learners' vocabulary learning in a foreign language, virtually during pandemic (Covid-19). These platforms and web pages provide different activities that are fun, interactive, and produce students' interest in learning new words. With findings is concluded that with the appropriate use of the technological resources inside the virtual classroom, students can increase their vocabulary in the English language in an innovative, creative, and motivational way.